Preventing AI Crime Towards A New Legal Paradigm: Lessons From United States - Wisnubroto, Aloysius; Hilaire Tegnan (Lembaga Contrarius Indonesia, 2025)
Indonesia has several laws to address AI-based crimes; however, the legal and criminal justice systems fail to address technology and AI-based crimes. This study aims to answer questions regarding the causes of the legal system in Indonesia having problems in resolving artificial intelligence-based crime cases and how the legal paradigm is developed and operationalised to anticipate the development of artificial intelligence-based crimes. This research employs a juridical-normative method and comparative law studies. The study shows that, firstly, positive criminal law with a legal-positivistic paradigm does not address adequately the dynamic and complex nature of AI-based crimes, which significantly impact social change. Learning from the US judicial system, which allows for the formation of legal sources through judges’ decisions, the resolution of AI crime cases in Indonesia needs to begin with liberation from the shackles of rigid legal texts. Secondly, to anticipate the development of AI crimes, it is essential to optimise the applicable criminal law through a new law enforcement paradigm developed from the principles of progressive law. This includes applying the principle of law for humans and the pillars of search, liberation, and enlightenment as foundational elements for legal innovation. By embracing the flexibility of the progressive legal paradigm, Indonesia can anticipate to changes in society and effectively manage the growth of AI-based crimes.